Execution of the ECtHR Judgment in Beizaras and Levickas v. Lithuania Case: Effectiveness and Legal Implications - Bruskina, Nika (Teisė, 2023)
In Beizaras and Levickas v. Lithuania case (Application No. 41288/15), the European Court of Human Rights found violations of the Convention for the Protection of Human Rights and Fundamental Freedoms as the Lithuanian law enforcement authorities had failed to start pre-investigation into allegations of homophobic hate speech directed against the applicants and the applicants thus suffered discrimination on the grounds of their sexual orientation. On 1 December 2021 the Committee of Ministers of the Council of Europe, supervising execution of the final judgment of the Court, welcomed the execution measures taken by the Lithuanian authorities and decided to continue the examination of Beizaras and Levickas case under the standard procedure instead of the enhanced one. First, this article recapitalutes the individual and general measures taken by the Lithuanian authorities seeking to execute the judgment of the European Court of Human Rights and discerns the factors which led to effective execution of the judgment. Second, the article demonstrates the positive impact of effective execution on any other similar cases pending both at the domestic level and before the ECtHR not only against Lithuania, but also against other Contracting States.
Keywords: execution of the judgment of the European Court of Human Rights; hate speech; private life; discrimination; sexual orientation; crime; pre-trial investigation